THE CASE AGAINST DRUG TESTING WHY THIS IS NOT THE TIME TO BEGIN USING A TECHNOLOGY THAT INVADES OUR PRIVACY AND JUST PLAIN DOESN'T WORK - OKEEFE,AM (Tufts Archival Research Center, 2007)
Article criticizing mass drug testing in companies. Suggests that it is unconstitutional, ineffective and an invasion of privacy.